Comorbidities and Treatment Strategies in Bullous Pemphigoid: An Appraisal of the Existing Litterature - Bech, Rikke; Kibsgaard, Line; Vestergaard, Christian (Frontiers in Medicine, 2018)
Bullous Pemphigoid is an autoimmune skin blistering disease. It is caused by deposition of auto antibodies along the dermal-epidermal border leading to inflammation. The antibodies are directed against anchoring filaments in the epidermis, but these antigens are also present in the neurological tissues and this has led to speculation of an association between multiple sclerosis and bullous pemphigoid. Additionally recent epidemiological studies have pointed at an increased risk of cardio-vascualr diseases and an increased moratality among he patients with bullous pemphigoid. In this mini review we present the recent findings in this area and as well as the treatment strategies when comorbidities are taken into consideration.